2019
DOI: 10.3390/coatings9040247
|View full text |Cite
|
Sign up to set email alerts
|

PVB/ATO Nanocomposites for Glass Coating Applications: Effects of Nanoparticles on the PVB Matrix

Abstract: Films made of poly(vinyl butyral) (PVB) and antimony-doped tin oxide (ATO) nanoparticles (NPs), both uncoated and surface-modified with an alkoxysilane, were prepared by solution casting at filler volume fractions ranging from 0.08% to 4.5%. The films were characterized by standard techniques including transmission electron microscopy, thermogravimetric analysis and differential scanning calorimetry (DSC). In the polymeric matrix, the primary NPs (diameter ~10 nm) aggregate exhibiting different morphologies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 54 publications
2
14
1
Order By: Relevance
“…This decrease may be due to the fact that the bonds between the polymer and the nanoreinforced source prevent the light from crossing. 3 Similar results of PVB-based nanocomposites for UV-vis curve was found also by Pizzanelli et al 59 In order to measure the radar absorption capabilities of the synthesized bare PVB and 1.0 wt.% Ag:Co nanocomposite film, a Vector Network Analyser (VNA) and double ridged horn antenna shown in Figure 8(b) were used. The 15 Â 20 cm copper plate mounted on the Styrofoam bed was located 1.3 m away from the antenna as a reference reflector.…”
Section: Optical and Microwave Properties Of Nanocompositessupporting
confidence: 76%
“…This decrease may be due to the fact that the bonds between the polymer and the nanoreinforced source prevent the light from crossing. 3 Similar results of PVB-based nanocomposites for UV-vis curve was found also by Pizzanelli et al 59 In order to measure the radar absorption capabilities of the synthesized bare PVB and 1.0 wt.% Ag:Co nanocomposite film, a Vector Network Analyser (VNA) and double ridged horn antenna shown in Figure 8(b) were used. The 15 Â 20 cm copper plate mounted on the Styrofoam bed was located 1.3 m away from the antenna as a reference reflector.…”
Section: Optical and Microwave Properties Of Nanocompositessupporting
confidence: 76%
“…In eqn (8), the contribution of methyl protons to w 0 0 NMR can be neglected since, at the investigated temperatures, the rotation about the C 3 axis certainly occurs at frequencies much higher than those explored here (see the ESI †). The contribution of protons in ''slow'' segments, related to the occurrence of dynamic heterogeneity and revealed by us through FID analysis, 29 can be safely neglected given their much longer T 1 . Indeed, dynamic heterogeneity has been reported for amorphous polymers up to a few tens of degrees above T g .…”
Section: H Ffc Nmr Relaxometrymentioning
confidence: 91%
“…No signal was detected for mobile water or ethanol in 1 H Free Induction Decay (FID) analyses of the PVB film. 29 On the other hand, no evidence of constrained ethanol was present in the 13 C Cross Polarization Magic Angle Spinning NMR spectra (see Fig. S1 in the ESI †).…”
Section: Sample Preparationmentioning
confidence: 99%
“…In spite of the large number of technological applications, only a few studies were reported concerning the dynamics of PVB [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Recently, PVB dynamics was investigated by some of us over broad frequency and temperature ranges by DS and 1 H field-cycling (FC) NMR relaxometry, focusing on a commercial sample [ 21 ].…”
Section: Introductionmentioning
confidence: 99%